Legal politics of bureaucratic reform in really good governance according to prophetical law - Asyikin, Nehru (Faculty of Law, University of Muhammadiyah Malang, 2020)
This research was conducted to analyse the political politics of bureaucratic reform. The politics of law in reforming government bureaucracy is actually useful for making improvements so that it becomes a public servant and realizing good governance. The problem with corruption, collusion and nepotism in the bureaucracy, is not because the legal umbrella in Indonesia is not strong but subjectively every state civil servant or civil servant does not yet have the full characteristics as in the prophetic concept. Through normative juridical research methods, this study tries to explore prophetic concepts to realize good governance. The results showed that it was hoped that this prophetic concept could become its future social ideals and as a guidebook for each ASN and PNS in its soul in carrying out its public service duties. Prophetic focuses on principles of behavior that originate from religious values. So that all executive, legislative and judicial branches can make moral ethics universally from the prophetic concept in providing services to the community in order to realize good governance